1963
DOI: 10.1149/1.2425910
|View full text |Cite
|
Sign up to set email alerts
|

The Electrochemistry of Nickel

Abstract: The anodic dissolution of nickel has been studied in acidified chloride, sulfate, and perchlorate solutions under a variety of nonpassivating conditions. The Tafel slopes at 45°C are approximately 0.085, 0.115, and 0.12, respectively. The lower value of the Tafel slope in chloride solutions is attributed to specific adsorption. The potential of the nickel anode is independent of Ni+2 concentration under conditions for which the back reaction is negligible, and no pH dependence has been found for pH of 1–2.5. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1964
1964
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…On the assumption that reaction [1] is under quasi equilibrium, the rate of reaction [2], v2, can be expressed as follows v~ k2' CNiOHo~ exp (F32" FE/RT) [1] where k2' is the formal rate constant of reaction [2] in electrical units and ~2' is the transfer coefficient for the reaction in the forward direction. The second possibility of producing Ni(OH)2 arises from a direct reaction between NiOH species and water, as indicated by reaction [5]. This reaction is preceded by the reaccommodation step represented by reaction [4], which is similar to that discussed for iron electrodes under comparable conditions (41).…”
Section: [Ni]k_l[nio ] + Hzomentioning
confidence: 93%
“…On the assumption that reaction [1] is under quasi equilibrium, the rate of reaction [2], v2, can be expressed as follows v~ k2' CNiOHo~ exp (F32" FE/RT) [1] where k2' is the formal rate constant of reaction [2] in electrical units and ~2' is the transfer coefficient for the reaction in the forward direction. The second possibility of producing Ni(OH)2 arises from a direct reaction between NiOH species and water, as indicated by reaction [5]. This reaction is preceded by the reaccommodation step represented by reaction [4], which is similar to that discussed for iron electrodes under comparable conditions (41).…”
Section: [Ni]k_l[nio ] + Hzomentioning
confidence: 93%
“…Davis and Barker [293] [315] shows that the tensile strength of 99 Foley [317] reported that the tensile strength of nickel increased with decreasing temperature, from 65,000 psi at room temperature to 97,500 psi at -120°C. Additional data at temperatures down to -320°F are given by International Nickel [86].…”
mentioning
confidence: 99%
“…Harb and Alkire used the experimental results of Kronenberg et aI. 12 to arrive at a Tafel expression The use of a Tafel expression is most appropriate for systems involving small jo values, as small values for the parameter jo imply that in passing any measurable current to the pit, one is immediately placed in the Tafel regime. These statements are supported analytically in Eq.…”
Section: Resultsmentioning
confidence: 99%
“…As a last note on the use of the Tafel expression, Kronenberg et al 12 found that the average-current/electrode-potential relationship is independent of the soluble nickel concentration when the Tafel condition applies, which ex: plains the lack of chloride ion concentration dependence in the exchange current density. That is, if a nickel concentration dependence in the anodic Tafel regime had been observed, it would imply that chloride ions are involved as anodic reactants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation